A discourse analysis of the Aboriginal and Torres Strait Islander COVID‐19 policy response - Monica Donohue; Ailie McDowall (Elsevier, 2021)
Abstract Objective: To analyse the implicit discourses within the COVID‐19 policy response for Aboriginal and Torres Strait Islander remote communities. Method: This paper uses Bacchi's 'What is the Problem Represented to Be' framework to analyse the Emergency Requirements for Remote Communities Determination under Subsection 477(1) of the Biosecurity Act 2015 (Cth). Results: Despite the leadership of community‐controlled health services and regional councils, and the actions of Aboriginal and Torres Strait Islander communities, the policy response constructs Aboriginal and Torres Strait Islander people as vulnerable and mobility as a problem that needs a law and order response. Conclusions: The policy response perpetuates an ongoing paternalistic discourse where Aboriginal and Torres Strait Islander people must be controlled for the sake of their health, informed by notions of Indigeneity as deficient. This stands in contrast with the work of community‐controlled health organisations, advocacy by Aboriginal and Torres Strait Islander people for and against restrictions, and examples of communities protecting themselves. Implications for public health: Unilateral government intervention creates limiting discourses of Aboriginal and Torres Strait Islander people. In contrast, ongoing COVID‐19 responses can build on the strengths of and work done by Aboriginal and Torres Strait Islander families, leaders, and communities.